Te hui kotahitanga mo te whaka-ora i roto i nga matauranga o te mate hinengaro = The intergenerational transmission of healing from the experience of mental illness : a thesis completed in partial fulfilment of a Master of Philosophy in Māori Studies - Naera, Rangi Lois (Massey University, 2015)
This thesis is based on stories and experiences of living with mental illness shared by members of my whanau to explore the research question What healing strategies do whanau with mental illness use to find wellness?. This topic was chosen because mental illness is intergenerational in our whanau weaving through five generations. The aim of this research was: to collect the stories of whanau members to understand their experiences of mental illness, particularly their experiences of healing; to develop a whanau model of healing; to reduce the stigma and discrimination related to mental illness; and, finally to educate the wider whanau, hapu, iwi and community and to facilitate their own healing pathways. A kaupapa Maori methodology that adopted a purakau approach was used for this research. A kaupapa Maori approach ensures that Maori culture, cultural knowledge and practices, such as purakau, underpin the research design and research practices. The research involved face to face interviews with four members of my whanau. Three key themes with a series of subthemes were from the data; 1. Wellness–as understood within the context of whanau, communicating; environment, awareness, causes and trauma 2. Behaviours associated with emotional and physical responses, denial and acceptance 3. Healing as it relates to identity, support, environment, spirituality, communicating and difference. The three themes were then used to create a whanau cycle of healing to illustrate how whanau moved from a state of unwellness to healing. Key stages of the cycle included awareness, unwellness, behaviours, denial, acceptance and healing. What is highlighted in this thesis are the healing techniques each individual uses to maintain wellness, the similarities such as health and fitness, busyness one’s belief in ‘God’ or spiritual other in the search for their identity as Maori an important aspect and strand in the healing steps to wellness. Recommendations from participants were simple; get to know me, be supportive and caring, don’t advise just listen, be non-judgemental, my unwellness doesn’t only affect me it affects my wider whanau but most importantly they recommended just being there present made a big difference. I didn’t feel alone knowing someone was there and I felt encouraged to find wellness. On a personal level this project created a tsunami of emotions that lead to the decision to write the thesis from the heart and focus on the stories of whanau. A purakau and kaupapa Maori approach enabled this to happen.
The intergenerational transmission of healing from the experience of mental illness
Keywords: Maori; Mentally ill; Family relationships; New Zealand; Mātauranga mate hinengaro; Whānau; Research Subject Categories::INTERDISCIPLINARY RESEARCH AREAS::Ethnicity